ERP upgrade process in a medium sized manufacturing company - Merta, Esko (fi=Turun yliopisto|en=University of Turku|, 2017)
As industry competition has grown over last years and decades, companies have realized that they need to improve the whole supply chain. Therefore, business competition is moving from among organisations to between the supply chains. Many organisations are making investments in developing and updating better technologies and systems, such as Enterprise Resource Planning system (ERP system) to take advantage of new functionalities, processes and features to streamline activities of an organisation. ERP upgrades usually happen in a cycle of three to five years and therefore, it is vital that organisations pay attention and invest in the ERP upgrade process. Even though the basic features an ERP system have stayed rather same, there are still new aspects introduced constantly to cover even wider range of business, such as Supply Chain Management (SCM). The continuous research on these topics is vital to ensure up-to-date knowledge. Consequently, this study was initiated because a manufacturing case company, and especially its SCM function, wanted to review their ERP upgrade project. This study investigated the ERP upgrade success by examining Critical Success Factors (CSFs) from the perspective of SCM function’s key-users. The research data was mainly collected by conducting interviews. Four key-users, project champion and six executives were interviewed. Documentation was applied as a secondary data source to confirm and enhance evidence from other sources. The author was working in this particular project and therefore participant-observation technic was applied. From the previous research, a five phase ERP upgrade process model was used as a frame for this study. The results of the study aligned with the theoretical framework greatly. All the seven main CSFs were identified. These were 1) Business plan and vision, 2) Change management, 3) Communication, 4) Project team composition, skills and compensation; 5) Project management, 6) Top management support and championship; and 7) System analysis, selection and technical implementation. From the entire company’s perspective the critical points were the lack of business plan and vision, project management and top management’s commitment. From the SCM function’s point of view the critical points were project team composition, skills and compensation; master data quality and the lack of documentation.